Arts and Cultural Tourism Management in Uttaradit, Phrae and Nan Provinces - Panyavuttrakul, Wasin; Tinakhat, Phisunt (Mekong-Salween Civilization Studies Journal, 2016)
The main purpose of this research was to study arts and cultural tourism in Uttaradit, Phare and Nan provinces. The research was conducted using Qualitative and Quantitative Methods. The proposed objectives were; 1) To define management model of the community’s arts and cultural tourism which consisted of 114 attraction sites divided into 4 groups of 48 temples, 13 museums, 25 art and craft centers and 24 attraction sites and accommodations. At present, the functions of these places are limited to being cultural learning centers rather than the actual site of arts and cultural tourism. 2) To develop a new management model and travel routes by focusing on arts and cultural tourism under the concept of “Culdutainments” which conceptualizes the gratification of cultural learnings. “Culdutainment” is collaboration of all relevant components and stakeholders on the complimentary basis which believed to deliver a sustainable tourism management. Furthermore, a total of 9 arts and cultural travel routes were considered under the theme of “Charms of East Lanna’s Handicraft. 3) To propose suggestions regarding policy which empowering the development of arts and cultural tourism model, attractive and distinctive new travel routes. This step involved 4 developmental platforms, 10 strategies, and 20 working schemes.